2022
DOI: 10.1101/2022.09.05.505584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unique case in whichKimoto-style fermentation was completed withLeuconostocas the dominant genus without transitioning toLactobacillus

Abstract: The Kimoto-style fermentation starter is a traditional preparation method of sake brewing. In this process, specific microbial transition patterns have been observed within nitrate-reducing bacteria and lactic acid bacteria during the production process of the fermentation starter. We have characterized phylogenetic compositions and diversity of the bacterial community in a sake brewery performing the Kimoto-style fermentation. Comparing the time-series changes with other sake breweries previously reported, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…We reported that Leuconostoc was dominant in the fermentation of Moto , and the switch of the predominant lactic acid bacteria from Leuconostoc to Lactobacillus was not observed in the fermentation process of this brewery (5). Several studies reported that Lactobacillus was detected in tanks (4,20)that can be directly in contact with raw materials and Moto .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We reported that Leuconostoc was dominant in the fermentation of Moto , and the switch of the predominant lactic acid bacteria from Leuconostoc to Lactobacillus was not observed in the fermentation process of this brewery (5). Several studies reported that Lactobacillus was detected in tanks (4,20)that can be directly in contact with raw materials and Moto .…”
Section: Discussionmentioning
confidence: 97%
“…All samples were collected in duplicate except for water. Samples shown as Moto are reported previously and utilized for comparison with the environmental samples in this study (5). The tools were utilized before the fermentation period of the fermentation starter, and only the tanks were in contact with the fermentation starter during fermentation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations